Molecular cloning, substrate specificity of the functionally expressed dihydroflavonol 4-reductases from Malus domestica and Pyrus communis cultivars and the consequences for flavonoid metabolism - Fischer, Thilo C; Halbwirth, Heidrun; Meisel, Barbara; Stich, Karl; Forkmann, Gert (Archives of biochemistry and biophysics, 2003)
Treatment with the dioxygenase inhibitor prohexadione-Ca leads to major changes in the flavonoid metabolism of apple ( Malus domestica) and pear ( Pyrus communis) leaves. Accumulation of unusual 3-deoxyflavonoids is observed, which have been linked to an enhanced resistance toward fire blight. The committed step in this pathway is the reduction of flavanones. Crude extracts from leaves are able to perform this reaction. There was previous evidence that DFR enzymes of certain plants possess additional flavanone 4-reductase (FNR) activity. Such an FNR activity of DFR enzymes is proved here by heterologous expression of the enzymes. The heterologously expressed DFR/FNR enzymes of Malus and Pyrus possess distinct differences in substrate specificities despite only minor differences of the amino acid sequences. Kinetic studies showed that dihydroflavonols generally are the preferred substrates. However, with the observed substrate specificities the occurrence of 3-deoxyflavonoids in vivo after application of prohexadione-Ca can be explained.